Crying in psychotherapy: an exploratory mixed-methods study on forms of emotional crying and associated therapeutic interventions - Gutjahr, Fabienne; Benecke, Cord (Research in psychotherapy (Milano)., 2024)
Emotional tears can be interpreted as expressions of our deepest inner lives, and yet they have largely been ignored in psychotherapy research. This study addresses this gap. Based on grounded theory and using a sequential mixed-methods design, we examined the interaction between therapist and patient during episodes of crying in video-recorded psychotherapy sessions. This resulted in two rating systems: one differentiates forms of patient emotional crying, and the other categorizes therapeutic interventions associated with crying. In this sample, including 46 video sequences from 32 therapy sessions, both rating systems were found to be reliable. To identify potential interactional patterns, we examined the statistical correlation between the two systems through multiple linear regression analyses. We found that certain forms of crying were associated with specific therapeutic interventions. Despite methodological limitations, the study contributes to a subject of clinical relevance that is still in its beginnings. To our knowledge, this is the first study to examine therapeutic events in episodes of crying in a process-oriented and comprehensive way.